Analysis of pesticide residues: organophosphates and pyre-throids in Solanum lycopersicum and Solanum tuberosum, and their potential impact on Public Health - Zea, Angélica Geovanna; Quichimbo, Paulina; Merchán, Evelyn; Caballero, Pablo (Journal of Ecohumanism, 2024)
In this study, the presence of pesticide residues in foods, specifically in tomatoes and potatoes, was investigated after harvesting in the Paute Canton-Ecuador. An information survey was car-ried out to determine the most relevant crops and pesticides in the study area. A qualitative analysis of organophosphates and pyrethroids was carried out in samples of Solanum lycoper-sicum and Solanum tuberosum using the thin layer chromatography technique. It was found that 80.00% of the tomato samples presented residues of organophosphate compounds and 30. 00% pyrethroid residues, while 66.7% of the potato samples tested positive for pyrethroids and 50.00% for organophosphates. These results indicate that there is a public health risk for people who consume foods with pesticide residues, even after washing and peeling tomatoes and potatoes, since the complete removal of these chemicals from foods cannot be guaranteed. This study highlights the importance of taking measures to minimize exposure to pesticides in food pro-duction and promote safer eating.